PENGEMBANGAN PROGRAM BK UNTUK MENGATASI PROKRASTINASI AKADEMIK - Rihya Syifa Qurrotu Ayuna; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Academic procrastination is one of the many obstacles in the student learning process. The negative impact of procrastination is that students can become individuals who are always looking for excuses when doing school assignments they don't like. This study used a descriptive method, non-probability sampling was carried out for convenience, consisting of 30 students of SMA class XI of the People's College 2. From the results of the student development instrument assessment conducted at the People's College 2 High School revealed that there were three lowest aspects, namely the Foundation of Religious Life , Emotional Maturity and Awareness of Responsibility. Of the three lowest aspects of Classical related to the Foundation of Religious Life, Emotional Maturity and Awareness of Responsibility. Aspect number one contains the Foundation of Religious Life with results (<4.43), aspect number 3 namely Emotional Maturity with results (<4.45) and aspect number 5 namely Awareness of Responsibility with values (<4.5). These results are significant with the results of the Academic Procrastination Scale (APS) instrument which shows the highest percentage of academic procrastination at 50.0%. So the BK teacher will create a BK program to overcome academic procrastination by focusing on BK services by providing Group Counseling services with the theme